O-115 Developing a computerised search to help UK general practices identify more patients for advance care planning: A feasibility study. (1st September 2015) - Mason, B; Boyd, K; Murray, Scott A; Steyn, J; Cormie, P; Kendall, M; Munday, D; Weller, D; Fife, S; Murchie, P; Campbell, C
Abstract : Background: Many patients with advanced conditions are not identified for advance care planning because they are not seen as having "palliative" care needs. In some countries General Practice information technology systems can improve care by identifying patients with deteriorating health so that they can be considered for an ACP and their care reviewed more systematically and effectively. Aim: The aim was to develop and test a computerised search of primary care records in routine clinical practice as a tool to improve patient identification for a palliative care approach. Methods: An iterative process of search design and testing followed by implementation and extended testing of the search output in clinical practice. A three-phase feasibility study: developing a computerised search, determining its ability to identify patients with deteriorating health from any advanced condition, and assessing how primary care clinicians use the results to improve patient care. The setting was twelve primary care teams in two Health Boards in Scotland. Results: The search identified 0.6% to 1.6% of patients in each practice who were not already on the practice palliative care register. Primary care clinicians judged that 30%–60% of these patients were at risk of dying or deterioration over the next 6–12 months. Discussion: The most common action taken by GPs was to start an electronic "anticipatory care plan", a specific Scottish form of advance care planning. Conclusion: It is possible to significantly improve the identification of patients for ACP and palliative care needs assessment using a computerised search. Time-efficient systems were important as was a generic tool for anticipatory care planning not linked to 'palliative' care.